2010
DOI: 10.1177/0093854810364106
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Failure to Register on Sex Offender Recidivism

Abstract: Failure to register (FTR) as a predatory offender recently supplanted criminal sexual conduct as the most common recidivism offense for sex offenders released from Minnesota prisons. To date, however, little is known about FTR. The authors attempted to address this gap by examining recidivism outcomes among inmates required to register as predatory offenders who were released from Minnesota prisons between 2000 and 2004. In particular, they analyzed whether an FTR offense (or history of any FTR offense) had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 18 publications
2
58
2
Order By: Relevance
“…The lack of significant findings for race, on the other hand, may be attributable to the relatively small sample size as well as the type of sample used in this study. Prior research on Minnesota prisoners has found that race is significantly associated with recidivism (Duwe, 2010;Duwe & Donnay, 2010;Duwe & Kerschner, 2008). However, because the majority of offenders in this study were from Hennepin and Ramsey counties, which have larger minority populations than the rest of the state, roughly 70% of the offenders examined here were minorities, a substantially higher percentage that that usually found among Minnesota prisoners (about 45%).…”
Section: The Impact Of Mcorp On Community Services and Programmingmentioning
confidence: 99%
“…The lack of significant findings for race, on the other hand, may be attributable to the relatively small sample size as well as the type of sample used in this study. Prior research on Minnesota prisoners has found that race is significantly associated with recidivism (Duwe, 2010;Duwe & Donnay, 2010;Duwe & Kerschner, 2008). However, because the majority of offenders in this study were from Hennepin and Ramsey counties, which have larger minority populations than the rest of the state, roughly 70% of the offenders examined here were minorities, a substantially higher percentage that that usually found among Minnesota prisoners (about 45%).…”
Section: The Impact Of Mcorp On Community Services and Programmingmentioning
confidence: 99%
“…A third way researchers attempt to measure recidivism is by gauging the extent to which individuals fail to register (FTR) with the police as sex offenders. Although FTR as a sex offender may not predict future sexual offending (Duwe & Donnay, 2010;Levenson, Letourneau, Armstrong, & Zgoba, 2010;Zgoba & Levenson, 2012), it has been found to predict general recidivism (Washington State Institute for Public Policy, 2006) and may tap into the antisocial or rule-breaking component of sexual offending (Levenson et al, 2010). It is therefore important that failure to report as a sex offender also be considered an outcome potentially predicted by the PICTS.…”
mentioning
confidence: 99%
“…In general, empirical data from Minnesota, New Jersey, New York, and South Carolina have not supported the hypothesis that sex offenders who fail to register are more sexually dangerous than their compliant counterparts (Duwe & Donnay, 2010;Levenson, Letourneau, Armstrong, & Zgoba, 2010;Levenson, Sandler, & Freeman, 2012;Zgoba & Levenson, 2012). Common findings across studies suggest that FTR is not significantly associated with sexual recidivism, though it is associated with nonsexual recidivism, and that FTR occurs in combination with a history of prior crimes and versatility in criminal offending.…”
Section: Ftr and Sexual Recidivismmentioning
confidence: 94%